Karakteristik Berbagai Formulasi Mikroorganisme Lokal (MOL) dan Pengaruhnya terhadap Pertumbuhan Tanaman Kangkung Darat (Ipomoea reptans (L.) Poir) - Swandi, Monica Kharisma; Jeniver, Jely; Nur Milah, Siti Ade; Safitri, Mutiara; Asyyifa, Inayah; Irawati, Irawati; Aliya, Putri; Khotimah, Khusnul; Sari, Astri Dian; Putri, Julian Eka; Sari, Nadila Puspita; Fatansyah, Firzan; Harita, Efita Karunia; Wiriyanti, Lesta Ayu; Indah Suryani, Putri Ayu (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2023)
Local microorganisms (MOL) contain fermented solutions made from various local resources. MOL solution has the potential to be used as liquid organic fertilizer because it contains microorganisms that can increase plant growth. This study aims to determine the characteristics of MOL based on different sources of microorganisms obtained from food ingredients typical of Bangka Belitung, as well as to determine their effectiveness on the growth of Ipomoea reptans (L.) Poir. This experimental study used a two-factorial completely randomized design (CRD), namely the type of MOL (without giving MOL (M0), MOL made from Bangka shrimp paste (M1), MOL made from rusip (M2), and MOL made from kitchen waste (M3)) and MOL dose (0% (D0), 15% (D1), 25% (D2), and 50% (D3)). Each treatment was repeated 2 times with a total of 32 experimental units. The variables observed were the characteristics of MOL after 1 week of incubation and the effect of giving MOL on the growth of Ipomoea reptans (L.) Poir 14 days after planting (HST). Data were statistically analyzed using SPSS software version 25 using the analysis of variance (ANOVA) method and Duncan's multiple range test (DMRT) with a 95% confidence level. The results showed that all MOL treatments were successfully fermented with characteristics of sour aroma, liquid texture, produce CO2, acidic pH, and presence of bacteria and mold. The results of ANOVA showed that the factor of giving the type of MOL and the interaction both factor had a significant effect on all observation parameters. However, the MOL dose factor did not significantly affect all observation parameters. Treatment of interaction the type and dose of MOL M2D1 can increase the response of the number of leaves, plant wet weight, plant dry weight, shoot dry weight, and root dry weight of Ipomoea reptans (L.) Poirs. The teratment of M1D3 increased the height response of Ipomoea reptans (L.) Poirs.